FACTORS OF EMERGENCE AND DEVELOPMENT OF TERROR PHOBIA AMONG SOUTHERN UKRAINE’S URBAN RESIDENTS - Kostiuchkov, Serhii; Pronin, Edward; Volkovych, Elena; Cherkashyna, Tetiana; Martynenko, Snizhana (Revista Inclusiones, 2020)
The purpose of the paper is to consider the main factors of the emergence and development of the fear of a terrorist attack, terror phobia, among Southern Ukraine’s urban residents. The authors emphasize that terrorist attacks have a destabilizing effect on individuals and societies as a whole, because they generate a space of fear, despair, and panic. Modern terrorism is seen as a phenomenon that creates a catastrophic threat not only to universal civilizational values –freedom, democracy, and security, but also to a sustainable lifestyle in a particular locality. Terrorism has become an integral attribute of modern planetary existence, a punishment for modern humanity, a kind of tribute to the altar of the new world order, a tragic fragment of the socio-political picture of the world, in which it is increasingly difficult to see the outlines of a new order or new chaos. The city of Kherson was chosen to be the research area as it is the centre of the region that borders the Russian-annexed Crimea and is geographically close to the combat zone in Eastern Ukraine. The location like that makes it topical to study the city’s population’s level of terror phobia, associated with the threat of being affected by a terrorist attack, perceived as a potential danger. The provisions put forward in the article are specified on the data of socio-empirical analysis of the individual components of Southern Ukraine’s terror sphere under the current circumstances.